International security the contemporary agenda - Dannreuther, Roland (Polity Press, 2013)
International Security is a cutting-edge analysis of the key security challenges and developments in the post-Cold War world. Drawing on a wide range of contemporary examples, from the Iraq war to the rise of China, it is an essential guide for students and policy makers seeking to understand the theoretical and empirical debates over the fast-changing nature of international security today. The book is organized into four main parts. Part 1 provides an analytical framework for the book, identifying the most significant post-Cold War shifts.